Three laboratory strains of spleen focus-forming virus: comparison of their genomes and translational products. - Ruscetti, S (1980)
The molecular properties of three laboratory strains of the spleen focus-forming virus were compared. All strains contain genetic sequences related to the env gene of mink cell focus-inducing murine type C leukemia viruses, and each strain codes for a glycoprotein of 50,000 to 52,000 daltons which shares specific immunological properties with the gp70's of mink cell focus-inducing viruses. In contrast to this constancy, gag gene products coded for by these strains vary significantly. The gag and env gene products are synthesized from separate mRNA's, and the mRNA for the env gene product is approximately 18S. Unlike other acute leukemia viruses, which can transform various undifferentiated cells, have large unique sequence cellular gene inserts fused to helper virus gag genes, and have one known genome-length intracellular mRNA, the spleen focus-forming virus transforms only specific hematopoietic stem cells, is an env gene rather than a gag gene recombinant virus, and has a second distinct and smaller class of intracellular mRNA. Our data therefore indicate that the Friend strain of the spleen focus-forming virus is a unique replication-defective acute leukemia virus.